Nimesulide with Metformin Lowers Inflammatory Markers in Women with PCOS - Reyam Mohammed Qasim; Maitham Ali Al-Rikabi; Edwar Z Khosho (Academia Open, 2025)
General Background: Polycystic Ovary Syndrome (PCOS) is a chronic endocrine and metabolic disorder characterized by hyperandrogenism, anovulation, and low-grade systemic inflammation, which contributes to insulin resistance and cardiovascular risk. Specific Background: Metformin, the first-line treatment for PCOS, has known anti-inflammatory properties, but whether its combination with selective COX-2 inhibitors such as nimesulide offers superior anti-inflammatory efficacy remains underexplored. Knowledge Gap: Evidence on adjunctive NSAID therapy targeting inflammation in PCOS is limited, and the combined effects of metformin and nimesulide on key inflammatory biomarkers, interleukin-6 (IL-6) and C-reactive protein (CRP), have not been systematically evaluated. Aims: This study investigated whether adding nimesulide to metformin enhances anti-inflammatory effects in women with PCOS. Results: In a non-randomized controlled study of 100 participants, both treatments significantly reduced IL-6 and CRP; however, combination therapy produced greater CRP reductions (p < 0.001), while IL-6 changes were comparable. Regression analysis identified total cholesterol and free testosterone as independent predictors of residual IL-6 levels (R² = 0.516). Novelty: This study is among the first to demonstrate synergistic anti-inflammatory effects of COX-2 inhibition with metformin in PCOS. Implications: Findings support the integration of metabolic and anti-inflammatory strategies for PCOS management and highlight the need for randomized trials assessing long-term efficacy and safety of adjunctive COX-2 inhibitors. Highlight: Combination therapy with nimesulide enhances metformin’s anti-inflammatory effect on CRP. IL-6 reduction was comparable between metformin alone and combination treatment. Total cholesterol and free testosterone independently predict residual inflammation. Keywords: PCOS, Metformin, Nimesulide, Inflammation, C-Reactive Protein